Morphology and Floral Biology of Twelve Water Lily Genotypes - Hoque, MA; Miah, MG; Hasan, MFA (Annals of Bangladesh Agriculture, 2023)
An experiment was conducted at the east nursery of Bangabandhu Sheikh Mujibur Rahman Agricultural University, Gazipur from July 2020 to June 2021 with a view to characterizing twelve water lily (Nymphaea nouchali) germplasm for cultivation in Bangladesh. The experiment was set up in a Randomized Complete Block Design with three replications. Rhizomes of each germplasm were planted in earthen tub of around 95 cm upper diameter and 40 cm depth was half filled with heavy clay soils. Characterization of the germplasm was then started at vegetative stage after 30 days of planting on the basis of flower color and thirty other traits. Results indicated that the number of leaves/plant at different days after planting varied significantly and counted the highest in NN 002 (26.0 at 30 DAP, 32.0 at 60 DAP and 29.7 at 90 DAP) and the lowest in NN 012 at 30 DAP (3.0) and 60 DAP (12.7); while at 90 DAP, the lowest was recorded in NN 010 (7.3). Leaf length varied from 8.2 cm (NN 007) to 31.4 cm (NN 008); while, leaf width varied from 7.5 cm (NN 007) to 28.6 cm (NN 002). The shortest time (36 days) to flowering was found in NN 008, conversely NN 011 took the maximum number of days (46) to flowering. Flower diameter ranged from 7.1 to 16.7 cm with the minimum in NN 007 and the maximum in NN 002. In NN 001, flowers were opened at night and closed in the morning; while in others, flower were opened in the early morning and closed either in the afternoon or in the evening. The duration of flowering in the genotypes ranged from 3-4 days. The genotypes NN 007 produced the maximum suckers per plant (13.3); and NN 003, NN 005, NN 008 and NN 009 did not produce any sucker. Flowers with shorter stalk from the base (< 30 cm) in NN 006, NN 007, NN 010, NN 011 and NN 012 can be used for producing flowers in small tub or urn. The genotypes NN 001, NN 002, NN 003, NN 004, NN 007, NN 008, NN 009 and NN 001 produced abundant pollen and they can be used in breeding program for developing more variation through crossing. All the genotypes should be maintained for further evaluation and next year use. Ann. Bangladesh Agric. (2022) 26 (2) : 97-111